Optimizing the sacrificial anode cathodic protection of the rail canal structure in seawater using the boundary element method. (April 2017) - Kim, Yong-Sang; Kim, Jeongguk; Choi, Dooho; Lim, Jae-Yong; Kim, Jung-Gu
Abstract: This paper deals with the cathodic protection design for axle/wheel and rail of ' rail-canal system ' in the ocean. The cathodic protection design was carried out using the boundary element method and was verified by the physical miniature tests. The optimum cathodic protection designs were determined based on the cathodic potential distribution and anode lifetime provided by the simulation. The unprotected physical miniature experienced widespread corrosion, whereas the protected miniature was covered with calcareous deposit, indicating that the surface was fully protected from corrosion. This study demonstrated that the boundary element can be applicable to the cathodic protection design of rail-canal structure.